2021
DOI: 10.1038/s41387-020-00148-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between different C-peptide level and insulin dose of insulin pump

Abstract: Background This study aims to explore the insulin requirement profiles, and analyze the related factors of type-2 diabetes mellitus (T2DM) with different C-peptide levels on insulin pump therapy. Methods A retrospective study was conducted on 271 T2DM patients treated with insulin pumps from 2016 to 2018. These patients were divided into groups according to the ratio of C-peptide at 2 h after meals to fasting C-peptide (C2h/C0), and the dosage of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Patients with LADA have low C‐peptide levels and show slower progression in islet cell destruction than those with type 1 diabetes mellitus 22 . C‐peptide is a marker secreted by islet β‐cells, and is not affected by exogenous insulin, which can reflect insulin content in the body and residual function of islet β‐cells 23 . Therefore, it is crucial for LADA patients to improve glycemic control and preserve β‐cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LADA have low C‐peptide levels and show slower progression in islet cell destruction than those with type 1 diabetes mellitus 22 . C‐peptide is a marker secreted by islet β‐cells, and is not affected by exogenous insulin, which can reflect insulin content in the body and residual function of islet β‐cells 23 . Therefore, it is crucial for LADA patients to improve glycemic control and preserve β‐cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Circular dichroism studies showed that all four binders were largely helical as designed and thermostable up to 95 °C (Supplementary Fig. 1b) C-peptide is a 31 residue peptide secreted by islet β cells that is made from the same precursorproinsulin -as insulin 24 . Measurement of plasma C-peptide levels is important for accurate classification and diagnosis of type I and type II diabetes 25 .…”
Section: Mainmentioning
confidence: 99%
“…C peptide is a polypeptide comprising 31 amino acids with a molecular weight of 3600. C-peptide is cleaved from pro-insulin, retained in secretory granules, and subsequently released into the bloodstream in levels equal to those of insulin during insulin biosynthesis 5 . The development of inter-chain disulfide bonds and accurate folding are both dependent on the presence of C-peptide, which fulfils an important role in the process of insulin manufacturing by acting as a connection between the A and B chains 6 .…”
Section: Introductionmentioning
confidence: 99%